Solar x-ray control of the ionospheric absorption measured by the sweep frequency method - Gupta, G.P. (Springer India, 1978)
The ionospheric absorption data measured by the sweep frequency method have been compared with the solar x-ray data in the band of 1-8 A during quiet- and disturbed-sun conditions. The degree of solar x-ray control of the ionospheric absorption and the corresponding limit of solar x-ray flux have been discussed.
Keywords: sweep frequency method; Control; absorption